Joining of hybrid semi-finished products from sheet metal by orbital forming - Hetzel, Andreas; Lechner, Michael; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2021)
Contrary demands like a reduction of carbon dioxide emissions and an increase in functionality are facing the manufacturing industry with growing challenges. When processing functional components, like synchronizer rings, conventional process chains, like shearing and subsequent joining, are reaching their limits due to an increased complexity of the components and a lack in efficiency, referring to the long process time. To meet these challenges, the strategy of lightweight construction combines the application of lightweight materials with efficient manufacturing processes and an innovative product design. One possibility within lightweight construction is the utilization of load-adapted hybrid components, featuring different material strength classes. In previous research, the process of orbital forming is used to manufacture semi-finished products with a varying thickness profile due to the specific radial material flow. This material flow should now be used to realize a permanent joint between materials of two different strength levels. Therefore, the process of orbital forming is modified to manufacture hybrid semi-finished products from a dual-phase steel DP600 and a naturally rigid aluminum alloy EN AW 5754, both with an initial thickness of 2.0 mm. Different joint geometries are cut by laser into a steel ring and the part is coaxially positioned around a basic aluminum disc inside a die and subsequently formed. The joint is investigated regarding the geometrical and mechanical properties, comparing a radial cross-section and the micro hardness distribution. In order to reveal the potential of orbital forming for a combined forming and joining operation, the axial as well as the peeling strength of the multi-material components are investigated and evaluated.<br
Keywords: Sheet-bulk metal forming; orbital forming; joining by forming; hybrid semi-finished products; lightweight design